Assessing the optimal inflation rate for the Kenyan economy - Auma, Laura (Strathmore University)
This study seeks to estimate the optimal level of inflation for the Kenyan economy that is favorable for its economic growth by using time-series dataset for the period 1981 to 2014. The study adopts a model proposed by Ademola & Aiwo (2006) to examine the existence of threshold level effects in the inflation-growth relationship. The estimated model suggests a 4 percent optimal level of inflation above which inflation retards economic growth.
Keywords: inflation; optimal inflation rate; economic growth